A case study on the sensitivity of downstream development to typhoon intensity and its initial location. (July 2017) - Chen, H.; Wang, K.; Wang, J. M.; Zhang, X. T.; Wang, Y. F.; Wang, W. L.
ABSTRACT: In this study, the sensitivity of downstream baroclinic development to a tropical cyclone's (TC's) intensity and its initial location relative to the upstream trough during the extratropical transition (ET) of Typhoon Malakas were examined. The downstream development intensity at the mid‐latitudes was mainly determined by two factors under the effect of ET, i.e. the strength of transporting low potential vorticity (PV) air downstream by the TC outflow and the strength of the PV gradient being disturbed in the mid‐latitude jet. The intensified TC had a stronger upper‐level outflow, and the intensified circulations associated with it could disturb the mid‐latitude PV gradient more strongly. Therefore, downstream development intensified, i.e. the trough‐ridge became more pronounced, and the jet became stronger. Downstream development seemed to be more sensitive to the TC location than its intensity. The TC, being closer to the trough, interacted with the mid‐latitude flow more strongly because the trough advanced and strengthened the process that the TC outflow transported low PV air to the mid‐latitudes in this situation. Moreover, the TC disturbed the PV gradient earlier and more strongly. The two effects intensified the downstream development. If the TC were weakened or moved away from the upstream trough, the outcome would be the opposite.